Transferable skills? Writing support in library courses for PhD candidates - Faber, Hege Charlotte Lysholm; Grote, Michael; Seland, Eli Heldaas (Septentrio Conference Series, 2021)
Courses in “generic” or “transferable” skills have during the last decade become an established part of the PhD-education in Norway, and they are today an important part of the academic libraries’ research support. At the same time academic writing centers and other writing support initiatives have spread widely in university libraries. “Writing” as a “transferable skill” has also advanced into the courses for PhD-candidates, accompanied by courses on search techniques, workflow issues and the publishing process. This paper will try to define actual PhD-candidate needs regarding the writing process and discuss how these can be addressed in courses in transferable skills at Norwegian university libraries. How dissertations may be structured, how research literature is reviewed or how literature searches are conducted varies strongly between different fields of research and depends a lot on subject-related factors like methodological requirements, genre conventions and research workflow. How can the libraries’ courses and internet resources meet the researchers’ demands for customized, relevant, project-related writing guidance, whilst the researchers’ projects are so totally different from each other in regard to genre, topic, method, theory and the role of writing in the research process? In the light of recent research on writing support we want to discuss current practices in courses, workshops and guidance for PhD-candidates in Norwegian university libraries and make some practical suggestions for writing education on PhD level.